Air Bubbles Mimic Disc Herniation in MRI after Cervical Epidural Block - Kim, Tae Sam (The Korean Pain Society, 2010)
Magnetic resonance image (MRI) is the most sensitive imaging test of the spine in routine clinical practice. Unlike conventional x-ray examinations and computed tomography scans, high-quality magnetic resonance images can be assured only if patients are able to remain perfectly still. However, some patients find it uncomfortable to remain still because of pain. In that condition, interlaminar cervical epidural injections can reduce pain and allow the procedure. When using air with the "loss of resistance" technique in epidural injections to identify the epidural space, there is the possibility of injected excessive air epidurally to mimic a herniated disc. We describe a case report of epidural air artifact in a cervical MRI after cervical epidural injections.